2022
DOI: 10.1002/ente.202201164
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐π‐Acceptor N‐Methyl‐4,5‐Diazacarbazole Based Ultra‐High Performance Organic Solar Cells: A Density Functional Theory Study

Abstract: The organic conjugated semiconductors have attracted the immense attention of scientists due to their pivotal role during charge transfer processes in organic solar cells (OSCs), [1] light-emitting diodes (LEDs), [2] and organic fields transistors (OFETs). [3] As compared to the commercially used inorganic materials, organic semiconductors are superior in their abundance, easy fabrication, low cost, flexibility, and extended π-conjugation. [4,5] In photovoltaic and solar cell devices suitable electronic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…MEPs are assessed to elucidate the quantitative representation of intermolecular charge distribution between the donor and acceptor regions of a molecular system 47 . MEP surfaces resemble a cloud with three main colors, each indicating a specific strength of the molecule's electrostatic potential.…”
Section: Molecular Electrostatic Potential (Mep)mentioning
confidence: 99%
“…MEPs are assessed to elucidate the quantitative representation of intermolecular charge distribution between the donor and acceptor regions of a molecular system 47 . MEP surfaces resemble a cloud with three main colors, each indicating a specific strength of the molecule's electrostatic potential.…”
Section: Molecular Electrostatic Potential (Mep)mentioning
confidence: 99%
“…Cyanostilbene appended donor–π–acceptor (D−π–A) type systems, where the cyano moiety acts as the acceptor (A), are the more straightforward model for a comprehensive understanding of the effect of positional isomerism of α and β analogs of cyanostilbene because it allows flexibility in molecular design by changing either conjugating moiety (π) or donor unit (D) systematically. , Such systems are capable of fabricating excellent hole and electron transport facilities and executing push–pull effects, allowing electron transfer from the donor to the acceptor through the conjugated π-units. Furthermore, D−π–A architecture having functionalized acrylonitrile compounds offers better nonlinear optical (NLO) performance. For example, Singh and co-workers recently synthesized a series of cyanostilbene-based D−π–A systems containing the 9,9-dimethyl-9 H -fluoren-2-amine type of chromophores and observed a significant enhancement in the first hyperpolarizability and related intrinsic hyperpolarizability by modulating the π-conjugation pathways . In a continued work, the same group compared the first hyperpolarizabilities by extending the π-conjugation of D−π–A systems and found that lengthening of π-conjugation beyond a certain limit hardly improves the NLO response.…”
Section: Introductionmentioning
confidence: 99%